Troponin I Changes in Patients with Subarachnoid Hemorrhage - Sarker, A; Hoque, MA; Khan, MMR; Rahman, MK; Alam, SM; Majumder, S; Sardar, MAH; Hasan, MA (TAJ: Journal of Teachers Association, 2018)
Background : Subarachnoid hemorrhage (SAH) is a catastrophic neurological event. Aside from its neurological morbidities, SAH is associated with significant medical complications. Cardiac manifestations are common and can impact morbidity and mortality in SAH patients. Myocardial enzyme release occur frequently after Subarachnoid hemorrhage that reflect adverse intracranial events .These changes often are unrecognized or misinterpreted, potentially placing patients at risk for inappropriate management. Objective : The aim of this study was to assess Troponin I changes after acute SAH and these changes were compared with neurological severity. The result of the study might be helpful for better understanding diagnostic and therapeutic implications of acute neurocardiogenic injury after SAH. Patients and methods : This cross sectional descriptive study was conducted over 30 patients with SAH in medicine, neuromedicine and intensive care unit of Rajshahi Medical College Hospital during the period of January 2015 to December 2016. Predictor variables reflecting demographic (age, sex, occupation), hemodynamic (pulse, systolic and diastolic blood pressure) and neurological (WFNS score) informations were recorded. We evaluated their cTnI level, which had been measured at admission. A cTnI level above 0.12 ng/ml was defined as an indicator of cardiac injury following SAH. Results : Out of 30 patients 26.7% were both in between 40-49 years and 60-69 years age group & 50% were male and 50% were female. Among the risk factors 60% of patient had history of hypertension, 40% smoking, 10% Diabetes mellitus and 3.3% alcohol abuse. On admission the mean GCS was 12.53±2.69,. The most frequently occurring WFNS grading were grade 1 and grade 4 (both were 43.3% of patients). Out of Thirty, 43.3% of patients demonstrated elevations of Troponin I. WFNS score ≥ 3 (92.3%, p = <0.001) significantly correlated with elevated Troponin I concentration. Conclusion : serum troponin I reveal a higher incidence of myocardial injury in patients with SAH. The present study also demonstrates that raised serum cTnI is associated with more severe neurological injury. These findings support a neurocardiogenic cause of cardiac injury after SAH. TAJ 2014; 27(2): 39-43